2017
DOI: 10.7860/jcdr/2017/27309.10442
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Quality of Life using the Oral Health Impact Profile (OHIP-14) in Subjects with and without Orthodontic Treatment need in Chennai, Tamil Nadu, India

Abstract: Hence, it is stated that there is an urgent need to educate the school children and in turn their parents regarding the malocclusion for its treatment to prevent any effect on quality of life of the young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Similarly, the study provides that the psychosocial behavior of the individuals gets impacted by the tooth loss and untreated decay, reducing the self-esteem of an individual 11. The mean scores of Group I subjects were lower than that of Group II subjects for all the aspects of QoL and the total scores; although, there was no statistically significant difference between the 2 groups 12. The difference in the financial QoL was dependent on the special type of diet which was taken following the procedure.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, the study provides that the psychosocial behavior of the individuals gets impacted by the tooth loss and untreated decay, reducing the self-esteem of an individual 11. The mean scores of Group I subjects were lower than that of Group II subjects for all the aspects of QoL and the total scores; although, there was no statistically significant difference between the 2 groups 12. The difference in the financial QoL was dependent on the special type of diet which was taken following the procedure.…”
Section: Discussionmentioning
confidence: 87%
“…Malocclusion is a common disease that impairs occlusal function, increases the incidence of caries, causes psychological discomfort, endangers health and reduces the quality of life 13 . An epidemiologic survey in America showed that 57% to 59% of each racial group has at least some degree of orthodontic treatment need 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion usually impairs the occlusal function causing psychological discomfort which will eventually result in the reduced quality of life. 25 …”
Section: Discussionmentioning
confidence: 99%